Uruguay's banking system exposure to transition risk - Andrea Baron; Helena Rodríguez (Latin American Journal of Central Banking (LAJCB), 2025)
The uncertainty implied in the transition to a low carbon economy introduces new challenges to central banks to forecast potential output, the output gap and inflation. It also poses significant challenges in terms of financial stability, to the extent that banks' loan portfolios could be highly exposed to vulnerable sectors. We present and apply two methodologies, one emissions-based and the other sector-based, to measure Uruguay's exposure to transition risk in terms of product, exports and credit. The results account for a relevant exposition, both from the perspective of the banking system and at a macro level. This reaffirm the necessity of integrating transition risk into the analyses and forecasts. Furthermore, there is a continued need to progress along pathways that evaluate and quantify this risk at both macroeconomic and financial levels.
Keywords: E58; Q54; 330; Banking system; Climate change; Transition risk; Uruguay